KAJIAN KARAKTERISTIK LALU LINTAS DAN EVALUASI ALTERNATIF PENINGKATAN KAPASITAS RUAS JALAN MAJAPAHIT KOTA SEMARANG (STUDI KASUS : SEGMEN JALAN DEPAN POLSEK PEDURUNGAN SAMPAI PASAR PENGGARON): KAJIAN KARAKTERISTIK LALU LINTAS DAN EVALUASI ALTERNATIF PENINGKATAN KAPASITAS RUAS JALAN MAJAPAHIT KOTA SEMARANG (STUDI KASUS : SEGMEN JALAN DEPAN POLSEK PEDURUNGAN SAMPAI PASAR PENGGARON) - Himam, Muhamad Khudza Alfi; Hadi, Tjokro; Mahardika, Vera; Nugroho, Fajar Jati; Pahlevi, Muhammad Reza (Bangun Rekaprima, 2026)
In the urban transportation system, Semarang is one of the cities with a high level of vehicle density, causing traffic congestion. This is also compounded by side obstacles, such as vehicles entering and exiting, stopped vehicles, parking on the roadside, pedestrians, and pedestrians. The Majapahit Road section is one of the intercity connecting roads. Thus, this road plays a very important role in serving a fairly large traffic flow. So that on this Majapahit Road section often experiences congestion that occurs not only at certain hours, because on this road section congestion is also caused by the presence of shopping centers, education, and shops. The important role of Majapahit Road results in vehicle queues and traffic delays, vehicle buildup, travel time delays (delays), and a decrease in the level of road service. Analysis of the performance of urban road sections, with performance indicators namely traffic flow (Q), capacity (C), degree of saturation (DS), free flow speed which is carried out with various performance indicators namely free flow speed (FV), as well as analyzing the level of service (Level of Service / LOS) on the road section. Based on calculations and analysis of this road segment in August 2025, the traffic flow (Q) value was 3,863.55 pcu/hour, the capacity value (C) was 2,821, and the degree of saturation (DS) was 1.37, exceeding 1. These values do not meet the required conditions. The free flow speed (FV) was 37.26 km/hour, and the level of service (LOS) was categorized as level F. Based on the calculation results in 2025, solutions/alternatives are needed to reduce the degree of saturation (DS) value by increasing the capacity value.